Geertz versus Levi-Strauss: latent structural dispositions in Geertz "theory of culture"? - Gordana Gorunović (University of Belgrade, 2016)
These are two authors, in Foucauldian terms that certainly belong to the most influential individuals in socio-cultural anthropology, as well as in the social sciences and interdisciplinary research more broadly. Claude Levi- Strauss became some kind of an "intellectual hero" during the domination of structuralism in the mid-twentieth century and during the 1960s, while Clifford Geertz was an ‘icon and ambassador’ of anthropology in the second half of the twentieth century. They are both one of the founders of the discourse theory. They not only established a distinct theoretical approaches and methods – structural (Levi-Strauss) and interpretative anthropology (Clifford Geertz), but through their intellectual authority they also inspired paradigms and intellectual movements making structuralism and "interpretation of culture" more than some passing episodes in the history of social though (in terms of "trendy ideas"). My aim is to make some parallels between these two authors, who despite all the differences that are evident in their epistemological discourses, theoretical approaches and methods (as well as in their ethnographic and anthropological writings itself) still have some similarities in their theorisation and interpretation of culture, which I would like to stress in this paper.